2004
DOI: 10.1177/1069072703257756
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Engineering Major Status From Mathematics Achievement and Interest Congruence

Abstract: This study proposed that precollege students’ standardized mathematics achievement score and the congruence between their occupational interests and engineering tasks would predict their second-year retention in college and the stability of their major. Binary response models were used to predict second-year major status (i.e., continue, transfer major, or dropout). High mathematics achievement was predictive of retention on campus and within the engineering major. Interest congruence predicted likelihood of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 38 publications
2
44
1
Order By: Relevance
“…Leuwerke et al (2004) found that academic preparation, as measured through the ACT Mathematics score, predicted whether entering engineering students persisted in their major. Their study did not assess the relations of high school GPA and first-year GPA on major persistence.…”
Section: The Roles Of First-year College Gpa and Academic Preparationmentioning
confidence: 97%
“…Leuwerke et al (2004) found that academic preparation, as measured through the ACT Mathematics score, predicted whether entering engineering students persisted in their major. Their study did not assess the relations of high school GPA and first-year GPA on major persistence.…”
Section: The Roles Of First-year College Gpa and Academic Preparationmentioning
confidence: 97%
“…A great deal of research on college major choice has been grounded in theories focused on either personality or person-environment fit (Allen & Robbins, 2008;Larson, Wei, Wu, Borgen, & Bailey, 2007;Leuwerke, Robbins, Sawyer, & Hovland, 2004;Porter & Umbach, 2006;Wessel, Ryan, & Oswald, 2008), previous academic performance (Allen & Robbins, 2008;Leuwerke et al, 2004;Trusty, 2002;Turner & Bowen, 1999;Wessel et al, 2008), self-efficacy (Larson et al, 2007;Lent, Sheu, Singley, Schmidt, Schmidt et al, 2008;Nauta & Epperson, 2003;Scott & Mallinckrodt, 2005), contextual factors related to the student's background (Malgwi et al, 2005;Turner & Bowen, 1999), or a combination of the aforementioned. This large body of literature makes clear that numerous factors affect college major choice; however, the relative influence of each factor tends to vary by study focus and design.…”
Section: Major Choice Theory and Major Persistencementioning
confidence: 99%
“…In contrast, past studies suggested that pre-college academic measures, such as high school GPA (Allen & Robbins, 2008;Crisp et al, 2009;King, 2015), SAT math score (Crisp et al, 2009), and ACT score (Allen & Robbins, 2008;Leuwerke et al, 2004), were significantly associated with major persistence.…”
Section: Discussionmentioning
confidence: 49%
“…The set of predictor variables used in the discrete-time hazard model, shown in Equation 1, was selected according to previous studies on college major persistence (Allen & Robbins, 2008), persistence in a STEM major (Crisp, Nora, & Taggart, 2009;King, 2015;Leuwerke, Robbins, Sawyer, & Hovland, 2004), and choice of college major (Pike, 2006;Porter & Umbach, 2006). Variables used in the model were chosen on the basis of restricted information available from the Office of Institutional Research.…”
Section: Predictor Variablesmentioning
confidence: 99%